2001
DOI: 10.1103/physrevlett.86.1362
|View full text |Cite
|
Sign up to set email alerts
|

Complete Screening and QuasiatomicMVVAuger Line Shapes due to Double Core Ionization

Abstract: MVV spectra of Rh, Pd, and Ag were measured with and without ionization of their L3 levels. Extra (MMMVV) structure corresponds to the M45M45-->M45VV transition following the L3M45M45 transition. We interpret the MMMVV structure for Pd as quasiatomic in nature from its similarity to the corresponding Ag spectral shape and from its agreement with atomic calculations. The Pd quasiatomic MMMVV spectrum arises from a two final-state hole bound state in the Pd d band filled by screening of the core holes. These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The values of the binding energy of features in EDC observed in the present work are slightly different from those of Björneholm et al [6] and two lines found in the present work are missing in their spectrum. The XPS 3p lines are explainable in terms of the multiplets formed by the electronic configuration of 3p 5 3d 9 . The lifetime of this final state is very short and the 3d hole is destroyed through screening by conduction electrons.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The values of the binding energy of features in EDC observed in the present work are slightly different from those of Björneholm et al [6] and two lines found in the present work are missing in their spectrum. The XPS 3p lines are explainable in terms of the multiplets formed by the electronic configuration of 3p 5 3d 9 . The lifetime of this final state is very short and the 3d hole is destroyed through screening by conduction electrons.…”
Section: Resultsmentioning
confidence: 96%
“…(8) In the range 76 hν 67 eV, the location of the highest peak, the apparent peak of the two-hole-bound-state band, deviates from the constant-binding-energy line for ε b = 6.3 eV. (9) The complete merger of the MVV sCK band and two-hole-bound-state band occurs in the region 70 hν 66 eV. (10) The change in the profile of the MVV sCK band cannot be interpreted in terms of the intensity changes of the satellites at ε b = 11 and 13.5 eV caused by resonance.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations